Social Status Concerns and the Political Economy of Publicly Provided Private Goods - Jana Friedrichsen; Tobias König; Tobias Lausen (The Economic Journal, 2021)
We analyse the political economy of the public provision of private goods when individuals care about their social status. Status concerns motivate richer individuals to vote for the public provision of goods they themselves buy in markets: a higher provision level attracts more individuals to the public sector, enhancing the social exclusivity of market purchases. Majority voting may lead to a public provision that only a minority of citizens use. Users in the public sector may enjoy better provision than users in the private system. We characterise the coalitions that can prevail in a political equilibrium.
Keywords: H42; D72; 330; in-kind provision; status preferences; majority voting